Keterkaitan Antara Kelimpahan Zooplankton dengan Fitoplankton dan Parameter Fisika-Kimia di Perairan Jailolo, Halmahera Barat - Yuliana . (Maspari Journal : Marine Science Research, 2014)
Zooplankton have an important role in water especially in the food chain, this organism is a consumer  I which plays a major role in bridging the energy transfer from primary producers (phytoplankton) to living things are at  a  higher  trophic  level  (fish  and  shrimp).   This  research  aimed  to  analyze  the  relationship  between  the abundance  of  zooplankton  to  phytoplankton  and  phisic-chemistry  parameters  at  Jailolo  waters,  HalmaheraBarat.   The  research  was  conducted  in  February  2011.  The  observation  of  zooplankton  were  taken  from  7 stations by filtration method. The result showed that there were 7 genera of 4 (four) groups: Ciliate(1 genus), Crustaceae  (4  genera),  Rotifera  (1  genus),  and  Sarcodina  (1  genus).   Abundance  of  zooplankton  range  from 1,429 - 32,571 cell/m3, the highest on Gufasa and Tuada (32,571 cell/m3) and the lowest on Bobanehena (1,429 cell/m3).    The  value  range  of  zooplankton  biological  index  were  diversity  index  (H  ')  =  0.4506  to  1.5091, equitability index (E) = 0.6356 to 0.9710, and the  dominance index (D) = 0 , 2379 to .7222. There is  a close relationship  between  the  abundance  of  zooplankton  to  phytoplankton  abundance  and  physico-chemical parameters  of  waters,  with  a  coefficient  of  determination  (R2)  of  0.972  and  the  regression  equation  Y  =  - 7194397 - 0.0836 phytoplankton + 269630 temperature+ 6195 salinity + 140943 DO - 128086 pH.